Variation of volatile compounds among wheat varieties and landraces. (1st May 2015) - Starr, G.; Petersen, M.A.; Jespersen, B.M.; Hansen, Å.S.
Highlights: Significant differences in volatile profiles found between 81 bread-wheat samples. Landraces differ from modern varieties. Segregation of sample volatile profiles according to geographical origin. Abstract: Analysis of volatile compounds was performed on 81 wheat varieties and landraces, grown under controlled greenhouse conditions, in order to investigate the possibility of differentiating wheat varieties according to their volatile compound profiles. Volatile compounds from wheat samples were extracted by dynamic headspace extraction and analysed by gas chromatography–mass spectrometry. Seventy-two volatile compounds were identified in the wheat samples. Multivariate analysis of the data showed a large diversity in volatile profiles between samples. Differences occurred between samples from Austria compared to British, French and Danish varieties. Landraces were distinguishable from modern varieties and they were characterised by higher averaged peak areas for esters, alcohols, and some furans. Modern varieties were characterised by higher averaged peak areas for terpenes, pyrazines and straight-chained aldehydes. Differences in volatile profiles are demonstrated between wheat samples for the first time, based on variety. These results are significant to plant breeders and commercial users of wheat.